Analisis Peran Platform Digital Dalam Meningkatkan Strategi Pemasaran Dan Penjualan UMKM Di Tepi Laut Tanjungpinang - Shella, Shella; Elisa; Everlin, Everlin; Shelia, Shelia; Sinta, Zona Kharisma (Jurnal Ilmiah Raflesia Akuntansi, 2025)
— This study aims to analyze the role of digital platforms in enhancing marketing strategies and sales of MSMEs in Tepi Laut Tanjungpinang. The research employs a qualitative method with a direct interview approach. The study focuses on five MSMEs: Pisang Kembung Viral, Corndog Tarik Lumer, MK Dimsum, Teh Tarik Malaysia Brother, and Es Jeruk Kiamboy. Interviews were conducted on March 2, 2025, to gather insights into digital marketing strategies and the adoption of digital payment systems, particularly QRIS. The findings indicate that most MSMEs have utilized social media platforms like Instagram, but their usage remains limited. Some MSMEs have adopted QRIS, yet its effectiveness varies depending on customer habits in conducting cashless transactions. The study concludes that digital platforms hold significant potential for improving marketing and sales performance among MSMEs. However, more optimal strategies are needed to maximize their utilization. MSMEs should actively manage social media, enhance customer awareness of digital payments, and collaborate with online food delivery platforms to expand market reach.